Internet Of Things Based Wireless Sensor Network System For Water Quality Monitoring - Kamaludin, Kamarul Hafiz (2018)
Generally, rivers are the main resource of water for living thing. The river's water quality affects our health directly which can be harmful if we consume contaminated water. Thanks to the advancement of technology in current water quality monitoring (WQM) for safe water consuming. Basically, on-site WQM and continuous WQM are being extensively deployed in Malaysia. The on-site method provide high mobility, low operation cost and low probability of theft problem or equipment damage as there is no fixed installation at WQM spot is required. However it vulnerable to high probability of human error due to manual operation and non-consistent real-time data solution. Meanwhile, the continuous WQM or also known as automatic station-based WQM provides consistent real-time data solution with no human error during WQM process. But its disadvantages are low mobility, high probability of theft problem due to fixed equipment installation and involve high operation cost. Therefore, the objective of this study is to design a hybrid WQM system which can improve the current issues of both WQM methods through multiple wireless technologies embedment. The Radio Frequency Identification (RFID) system, WSN and internet bandwidth are consolidated into one platform of Internet of Thing (IoT) ecosystem namely IoT for water quality monitoring (IoT-WQM) system is studied. The proposed IoT-WQM system provides real-time monitoring on pH level and ambient temperature and enhanced with mobile alert triggering system through mobile device. To achieve the objective of this study, a prototype of proposed system are designed and developed based on literature reviews. Then it was analyzed by several series of experiment to investigate its performance and characteristic. This includes frequency verification, energy analysis, anti-collision detection analysis, WSN range test analysis, throughput and network latency. Based on conducted analyses, the average percentage difference for pH measurement during wet weather condition are 0.31 % for IoT-WQM system and 0.28 % for standalone RFID system. While, the average percentage difference during dry weather condition for the IoT-WQM and standalone RFID systems are 0.36 % and 0.33 % respectively. The analysis of anti-collision detection shows a 100 % receiving efficiency of the transmitted information packet by transmitting IoT-WQM tags. The maximum outdoor range test result in LoS environment of IoT-WQM system based on extrapolation is 100 % identical with the XBee Pro specification which is 6.5 km. Meanwhile, the maximum reading of average RSSI value for multihop NLoS communication is -85 dBm at 1000 m distance. The average throughput of IoT-WQM system is 0.23% slightly higher than standalone RFID system for both encrypted and unencrypted modes. Meanwhile, the average latency of IoT-WQM system is slightly higher than standalone RFID system for both encrypted and unencrypted mode which are 0.12 % and 0.45 % respectively.